ANALISIS KINERJA PEMELIHARAAN BERDASARKAN SAFETY PERFORMANCE INDICATOR MENGGUNAKAN RELIABILITY MAPPING - Mufti Arifin (Jurnal Teknologi Kedirgantaraan, 2020)
–ICAO Annex 19 Safety Management required safety measurement using Safety Performance Indicator (SPI). SPI parameter determined by operator. One of example is maintenance parameter related with accident or incident. SPI maintenance consist of Pilot Report, Dispatch Reliability, Deferred Maintenance (DMI), Service Difficulty Report, Air Turn Back, Rejected Take Off, and Repeated Defect. Some of SPI parameters have correlations. Simulation using reliability mapping with varies maintenance scenario to see correlation between Deferred Maintenance Item, Repeated Defect, and Technical Interruption which is used for Dispatch Reliability calculation has been done. Maintenance performance analysis also simulated with this method. The result shows cause effect correlation in two and one way between three SPI parameters. Maintenance performance could be predicted using reliability mapping mainly for time needed for defect rectification and repeated defect, repeated DMI, or repeated technical interruption